Biocompatible Snowman-like Dimer Nanoparticles for Improved Cellular Uptake in Intrahepatic Cholangiocarcinoma - Ruyin Chen; Xingqun Pu; Rongrong Liu; Xiaomeng Dai; Fangfu Ye; Chunxia Zhao; Peng Zhao; Jian Ruan; Dong Chen (MDPI AG, 2023)
Intrahepatic cholangiocarcinoma (ICC) is one of the most aggressive types of human cancers. Although paclitaxel (PTX) was proven to exert potent anti-tumor effects against ICC, the delivery of PTX is still challenging due to its hydrophobic property. Nanoparticle (NP)-based carriers have been proven to be effective drug delivery vehicles. Among their physicochemical properties, the shape of NPs plays a crucial role in their performance of cellular internalization and thus anti-tumor efficacy of loaded drugs. In this study, dumbbell-like and snowman-like dimer NPs, composed of a polylactic acid (PLA) bulb and a shellac bulb, were designed and prepared as drug nanocarriers to enhance the efficiency of cellular uptake and anti-tumor performance. PLA/shellac dimer NPs prepared through rapid solvent exchange and controlled co-precipitation are biocompatible and their shape could flexibly be tuned by adjusting the concentration ratio of shellac to PLA. Drug-loaded snowman-like PLA/shellac dimer NPs with a sharp shape exhibit the highest cellular uptake and best cell-killing ability against cancer cells in an in vitro ICC model over traditional spherical NPs and dumbbell-like dimer NPs, as proven with the measurements of flow cytometry, fluorescent confocal microscopy, and the CCK8 assay. The underlying mechanism may be attributed to the lower surface energy required for the smaller bulbs of snowman-like PLA/shellac dimer NPs to make the initial contact with the cell membrane, which facilitates the subsequent penetration through the cellular membrane. Therefore, these dimer NPs provide a versatile platform to tune the shape of NPs and develop innovative drug nanocarriers that hold great promise to enhance cellular uptake and therapeutic efficacy.